Interaction of phonons at superfluid helium - solid interfaces - Adamenko, I.N.; Nemchenko, E.K. (Condensed Matter Physics, 2014)
New method to obtain the interaction Hamiltonian of phonons at superfluid helium - solid interface is proposed in the work. Equations of hydrodynamic variables are obtained in terms of second quantization if helium occupies a half-space. The contributions of all processes to the heat flux from solid to superfluid helium are calculated based on obtained Hamiltonian. The angular distribution of phonons that are emitted by solid are found in different processes. It is shown, that all of exit angles of superfuild helium phonons are allowed. The obtained results are compared with experimental data and with previous theoretical works. У роботi запропоновано новий метод отримання гамiльтонiана взаємодiї фононiв на поверхнi роздiлу тверде тiло-надплинний гелiй. Отримано вирази для збурень гiдродинамiчних змiнних у термiнах вторинного квантування у випадку, якщо рiдина займає напiвпростiр. На основi отриманого гамiльтонiана обчислено вклади вiд усiх процесiв у потiк тепла з нагрiтого твердого тiла у надплинний гелiй. Отримано кутовi розподiли випромiнених твердим тiлом фононiв у рiзних процесах. Показано, що у випадку непружних процесiв немає заборон на кути вильоту фононiв у надплинний гелiй. Отриманi результати порiвнюються з результатами експериментальних та теоретичних робiт.